A Hybrid Energy Solution for the Sustainable Electricity Supply of an Irrigation System in a Rural Area of Zona Bananera, Colombia - Hernández, Juan Camilo Barrera; Moreno, Christian; Ospino-Castro, Adalberto; Robles-Algarin, Carlos Arturo; Tobón-Perez, Juan (International Journal of Energy Economics and Policy, 2021)
A hybrid energy system allows the integration of various technologies to meet energy demands competitively. These systems are widely used in rural areas with connection problems in the conventional electrical grid due to their economic and environmental advantages. Thus, this paper presents the design and simulation of a hybrid energy system that evaluates the suitability of using various generation sources such as photovoltaic energy, biomass, diesel generation and connection to the conventional electrical grid, in order to establish scenarios competitive to supply energy in an irrigation system of the Palmar de la Sierra experimental field, located in the municipality of Zona Bananera, Magdalena, Colombia. The sizing of the system was performed with Homer Pro software, with which technical, economic and environmental aspects of the studied scenarios were evaluated. The data of solar irradiance and the characteristics of the oil palm fruit peel, used for generation with biomass, were provided by the Cenipalma company. The results obtained show that the hybrid system (photovoltaic, biomass, diesel) can satisfy the demand of 2200 kWh/day of the irrigation system under study, using a connection to the electricity grid that allows the purchase and sale of energy. Keywords: Hybrid Energy System, Photovoltaic Energy, Biomass Gasification, Financial Analysis JEL Classifications: Q42, G32, G00, O13 DOI: https://doi.org/10.32479/ijeep.11014